PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA TANGERANG SELATAN - Rustinah, Nadia; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of Discipline and Motivation on Employee Performance in Employees of the Regional People's Representative Council of South Tangerang City, both partially and simultaneously. The method used in this study is a descriptive analysis method with a quantitative approach. The results of this study are that Discipline has a significant effect on Employee Performance with the regression equation Y = 20.173 + 0.491 X1, the correlation value of 0.467 means that both variables have a moderate relationship. The value of the coefficient of determination is 21.8%. Test the hypothesis obtained t count > t table or (3.089 > 2.007). Motivation has a significant effect on employee performance with the regression equation Y = 26.095 + 0.372 X2, the correlation value is obtained at 0.578 meaning that the two variables have a moderate level of relationship. The value of the coefficient of determination is 33.4%. Test Hypothesis obtained t count > t table or (5.106 > 2.007). Discipline and Motivation simultaneously have a significant effect on Employee Performance with the regression equation Y = 14,700 + 0.332 X1 + 0.307 X2, a correlation value of 0.651 means that both variables have a strong level of relationship. The value of the coefficient of determination is 42.4%. Test the hypothesis obtained F count > F table or (18.737 > 3.18).